A Case of Recurrent Acute Pancreatitis Due to Intra-Articular Corticosteroid Injection - Ungprasert, Patompong; Permpalung, Nitipong; Summachiwakij, Sarawut; Manatsathit, Wuttiporn (JOP. Journal of the Pancreas, 2014)
Context Corticosteroid is a well-established cause of drug-induced pancreatitis. However, acute pancreatitis from intra-articular injection of corticosteroid has never been described. Case report A 69-year-old male presented with acute abdominal pain and was diagnosed with acute pancreatitis. The patient had one episode of acute pancreatitis two year earlier. Both episodes occurred after intra-articular cortisone injection. Investigations for other causes of pancreatitis were negative. Conclusion We report the first case of acute pancreatitis from intra-articular corticosteroid injection. Physicians should be aware of this adverse reaction of corticosteroid that can even occur with local administration. Image: Bassett Medical Center. Cooperstown, NY, USA (logo)